Rationalization of Curriculum Implementation Based on Local Wisdom of Sad Kerthi - Candrawati, Putu; Paramartha , Wayan; Suasthi, I Gusti Ayu (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
This research is motivated by the suboptimal implementation of the Sad Kerthi local wisdom-based curriculum, resulting in the lack of full internalization of local wisdom values in the learning process. Furthermore, there are still challenges in integrating global education principles with local wisdom to align with the needs of students in the modern era. The main objective of this research is to analyze the implementation of the Sad Kerthi local wisdom-based curriculum to strengthen the relevance, effectiveness, and sustainability of education that aligns with local cultural values and global challenges. The object of this research is the philosophy of life of the Balinese people, which includes six main values. The research was designed as a qualitative study with a case study method. Data were collected through participatory observation, structured interviews, and document analysis. The results show that the rationale for implementing the Sad Kerthi local wisdom-based curriculum at GSB is based on the need to integrate Balinese local cultural values into modern education that is holistic, ecological, and sustainable. The results of this study indicate that students are better able to understand the connection between modern knowledge and Balinese local wisdom values, thus creating contextual, sustainable learning that is oriented towards cultural and environmental preservation. The implication is that implementing a curriculum that integrates local wisdom values can strengthen students' cultural identity while fostering concern for the environment and sustainable living.